Legal Conformity Between Rahn Tasjily And Fiduciary Guarantee And Obstacles To Implementation In Indonesia - Nurjihad (Prophetic Law Review, 2023)
The focus of this research is to provide solutions for the problem in the implementation of fiduciary guarantees and Rahn Tasjily. Rahn Tasjily is collateral in the form of goods for debts, with the agreement that only legal proof of ownership will be handed over to the recipient of the guarantee (murtahin), while the physical collateral (marhun) remains in the control and use of the guaranteed provider (rahin). This research aims to achieve two objectives: first, to examine the suitability of the fiduciary guarantee with rahn tasjily and second, to analyze the appropriate formulation to ensure the legal conformity of the fiduciary guarantee with rahn tasjily and its implementation in an engagement/transaction in accordance with sharia principles. This is normative legal research with a statutory and conceptual approach. The study concludes that: (1) Rahn Tasjily as regulated in the fatwa of the National Sharia Council of the Indonesian Ulema Council Number 68/DSN-MUI/III/2008 shares similarities or conformity with the provisions of Fiduciary Guarantee (Law No. 42 of 1999 concerning Fudiciary Guarentee). This conformity refers to the conformity between the object/collateral and the proof of ownership, instead of the form of the object. Both are also referred to as an accesoire agreement; (2) In order to ensure the legal conformity between the fiduciary guarantee and rahn tasjily and its implementation as a material guarantee in sharia financing without doubt, the legislators need to make changes to Law Number 42 of 1999 as a way to provide clear arrangements regarding the main engagements to be burdened with fiduciary guarantees, which include: conventional or sharia-based debt or financing agreements.Keywords: Fiduciary Guarantee, Rahn Tasjily, Sharia Financing. Kesesuaian Hukum Antara Rahn Tasjily Dan Jaminan Fidusia Serta Kendala Penerapannya Di Indonesia AbstrakFokus penelitian ini adalah memberikan solusi atas permasalahan dalam pelaksanaan jaminan fidusia dan Rahn Tasjily. Rahn Tasjily adalah agunan berupa barang utang, dengan perjanjian hanya bukti kepemilikan yang sah yang akan diserahkan kepada penerima jaminan (murtahin), sedangkan agunan fisik (marhun) tetap dalam penguasaan dan penggunaan. penyedia terjamin (rahin). Penelitian ini bertujuan untuk mencapai dua tujuan yaitu pertama, menguji kesesuaian jaminan fidusia dengan rahn tasjily dan kedua, menganalisis rumusan yang tepat untuk menjamin kesesuaian hukum jaminan fidusia dengan rahn tasjily dan implementasinya dalam suatu perikatan/transaksi di sesuai dengan prinsip syariah. Penelitian ini merupakan penelitian hukum normatif dengan pendekatan perundang-undangan dan konseptual. Kajian menyimpulkan bahwa: (1) Rahn Tasjily sebagaimana diatur dalam fatwa Dewan Syariah Nasional Majelis Ulama Indonesia Nomor 68/DSN-MUI/III/2008 mempunyai kesamaan atau kesesuaian dengan ketentuan Jaminan Fidusia (UU No. 42 Tahun 1999 tentang Jaminan Fudiciary). Kesesuaian yang dimaksud adalah kesesuaian antara benda/jaminan dengan bukti kepemilikannya, bukan bentuk bendanya. Keduanya disebut juga sebagai perjanjian accesoire; (2) Untuk menjamin kesesuaian hukum antara jaminan fidusia dengan rahn tasjily serta pelaksanaannya sebagai jaminan kebendaan dalam pembiayaan syariah tanpa keraguan, pembentuk undang-undang perlu melakukan perubahan terhadap Undang-Undang Nomor 42 Tahun 1999 sebagai upaya memberikan pengaturan yang jelas mengenai hal tersebut. perikatan utama yang dibebani dengan jaminan fidusia, yang meliputi: perjanjian utang atau pembiayaan yang konvensional atau berbasis syariah.Kata Kunci: Jaminan Fidusia, Rahn Tasjily, Pembiayaan Syariah.